ChemInform Abstract: Asymmetric Allylation/Ring Closing Metathesis: One‐Pot Synthesis of Benzo‐Fused Cyclic Homoallylic Amines. Application to the Formal Synthesis of Sertraline Derivatives. Issue 49 (3rd December 2013) - Fustero, Santos; Lazaro, Ruben; Herrera, Lidia; Rodriguez, Elsa; Mateu, Natalia; Barrio, Pablo
Abstract A stepwise process consisting of asymmetric allylation of imines of type (I) and following ring‐closing metathesis of the resulting dienes (III) is developed to synthesize cyclic homoallylic amines.